KESANTUNAN BERBAHASA DALAM DEBAT PILKADA DKI JAKARTA 2017 - Eriyani, Desta; Sinaga, Mangatur; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is titled Language Politeness in the Regional Head Election Debate DKI Jakarta 2017. The purpose in this study is to describe compliance and violations in the Regional Head Election Debate DKI Jakarta 2017. The method used is descriptive. Furthermore, the results of this study on data on the use of the language politeness in the regional head election debate DKI Jakarta as many as 5 data that comply with the maxim of politeness principle and 55 data that violated the maxim of politeness principle. As for the details of the maxim of politeness compliance, namely the award of 3 utterances, the maxim of simplicity of 1 utterance, and the maxim of agreement of 1 utterance, and the details of maxim of violation of the principle of politeness in language are wisdom found 29 utterances, maxim of appreciation of 11 utterances, maxim of simplicity of 9 utterances, and maxim of agreement of 6 utterances.Key Words: Politeness of Language, Debate